Vibrio natriegens: an ultrafast‐growing marine bacterium as emerging synthetic biology chassis. (16th July 2020) - Hoff, Josef; Daniel, Benjamin; Stukenberg, Daniel; Thuronyi, Benjamin W.; Waldminghaus, Torsten; Fritz, Georg
Summary: The marine bacterium Vibrio natriegens is the fastest‐growing non‐pathogenic bacterium known to date and is gaining more and more attention as an alternative chassis organism to Escherichia coli . A recent wave of synthetic biology efforts has focused on the establishment of molecular biology tools in this fascinating organism, now enabling exciting applications – from speeding up our everyday laboratory routines to increasing the pace of biotechnological production cycles . In this review, we seek to give a broad overview on the literature on V. natriegens, spanning all the way from its initial isolation to its latest applications. We discuss its natural ecological niche and interactions with other organisms, unveil some of its extraordinary traits, review its genomic organization and give insight into its diverse metabolism – key physiological insights required to further develop this organism into a synthetic biology chassis. By providing a comprehensive overview on the established genetic tools, methods and applications we highlight the current possibilities of this organism, but also identify some of the gaps that could drive future lines of research, hopefully stimulating the growth of the V. natriegens research community.